2017
DOI: 10.1038/cddis.2017.462
|View full text |Cite
|
Sign up to set email alerts
|

Activation of miR-34a impairs autophagic flux and promotes cochlear cell death via repressing ATG9A: implications for age-related hearing loss

Abstract: Age-related hearing loss is a major unresolved public health problem. We have previously elucidated that the activation of cochlear miR-34a is correlated with age-related hearing loss in C57BL/6 mice. A growing body of evidence points that aberrant autophagy promotes cell death during the development of multiple age-related diseases. The aim of this study was to investigate the role of miR-34a-involved disorder of autophagy in the pathogenesis of age-related hearing loss. Our results showed that miR-34a expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 61 publications
5
38
1
Order By: Relevance
“…We hypothesized that mitochondrial dysfunction was induced by a disturbance in mitophagy. Our previous study revealed that rapamycin can preserve mitochondrial function by initiating autophagy (Pang et al, 2017). We found that in cellular senescence, the disturbed autophagy flux assessed by the LC3 II and P62 proteins confirmed our hypothesis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We hypothesized that mitochondrial dysfunction was induced by a disturbance in mitophagy. Our previous study revealed that rapamycin can preserve mitochondrial function by initiating autophagy (Pang et al, 2017). We found that in cellular senescence, the disturbed autophagy flux assessed by the LC3 II and P62 proteins confirmed our hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…Auditory brainstem response (ABR) tests were conducted using the Tucker-Davis Technology (TDT) System III (Alachua, FL, USA) as previously described (Pang et al, 2017). In brief, mice were anesthetized, and subdermal needle electrodes were inserted at the vertex (active) and below the left ear (reference) and the right ear (ground).…”
Section: Auditory Brainstem Responsementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that miR-34a, which has been implicated in inducing senescence, cell cycle arrest, autophagy, and cell death [96], is also linked to ARHL in c57BL/6 mice [97]. In addition, upregulation of miR-34a in the aging cochlea was accompanied by impairment of autophagic flux, with an accumulation of phagophores and impaired autophagosome-lysosome fusion [98]. Together, these results suggest that autophagy may be a housekeeping mechanism necessary for cochlear cell survival during aging.…”
Section: Mitochondrial Quality Control and Autophagymentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small RNAs (18-25-nucleotide) that down-regulate the expression of target genes via binding to the 3′-untranslated region (UTR) and then participate in the cellular processes. There has been evidence to indicate miRNAs participate in the pathogenesis of AHL, including miR-34a (Huang et al 2017;Pang et al 2017)…”
Section: Discussionmentioning
confidence: 99%